Using Photovoice to compare recreational activities in four socially vulnerable Costa Rican communities - Juniu, Susana (2020)
Between the years 2017 and 2019, four qualitative research studies were conducted in four socially vulnerable communities in the province of San José, Costa Rica: Los Cuadros de Purral de Goicoechea, DosCercas de Damas de Desamparados, Tirrases de Curridabat, and Alajuelita (San Felipe, Concepción and Alajuelita Centro). The purpose of the project was to analyze, using the Photovoice methodology, the recreational activities carried out by groups of women and their communities, as well as the contextual factors that facilitated or hindered their recreational participation. This article highlights the comparison of the study results among the four communities. A total of 23 women participated in the study and took photographs for two weeks and selected the 16 images that best represented their experiences. Each community group analyzed and categorized their photos. The themes that had emerged in the four communities were analyzed by the researchers using the constant comparison method and content analysis. The results showed new themes including four factors that promoted recreation, five barriers that made it difficult, and nine types of recreational activities enjoyed in the communities. Not all the new themes were evident in the four locations. In all four communities, lack of hygiene, insecurity, and lack of facilities and poor maintenance affected participation in recreation. It was also found that the communities received support from local or national entities that favored recreational activities. It was concluded that the people of these communities participated in diverse types of recreational activities and that, in difficult conditions, they negotiated to do so, despite the fact that the barriers were more numerous than the factors that promoted recreation.